Determination of ethalfluralin in soy flour samples using MnO2-deep eutectic solvent based nanofluid for its preconcentration prior to GC-FID measurement - Gursoy, Selim; Bombom, Miray; Zaman, Buse Tugba; Turak, Fatma; Er, Elif Ozturk; Korkunc, Ummugulsum Polat; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2024)
In the present study, a dispersive solid-phase extraction based on colloidal gel is presented for rapid/efficient determination of ethalfluralin with high precision and accuracy. The synthesis of colloidal gel was accomplished by combining manganese dioxide (MnO2) nanoparticles with the deep eutectic solvent (DES) as the preferred ionic fluid. Using a one-factor-at-a-time approach, variables affecting the extraction efficiency of the developed method were optimized to achieve the highest extraction efficiency and stability for the determination of the target analyte. In line with data obtained, the limit of detection value for the target analyte was determined to be 10.2 mu g/kg. In order to demonstrate the accuracy/applicability of the developed method in complex matrices, different soy flour samples were utilized, and extraction procedures were conducted under pre-determined optimal method conditions. Matrix matching calibration strategy was applied to spiked samples, followed by the determination of percent recovery results ranging between 92.1 and 114.2%.
Keywords: Pesticide; Microextraction; Manganese dioxide; Gas chromatography-flame ionization detector (GC FID); Nanofluid; Deep eutectic solvent; MASS-SPECTROMETRY; LC-MS/MS; PESTICIDES; NANOPARTICLES; DEGRADATION; ABSORPTION; MECHANISMS; Chemistry